Experience, Emotion, and Eudaimonia: A Consideration of Tourist Experiences and Well-being. (May 2017) - Knobloch, Uli; Robertson, Kirsten; Aitken, Rob
Experiential marketing and the quest to create memorable and extraordinary customer experiences have become central to tourism. However, implementing the concept of experiential marketing has been problematic due to a lack of knowledge regarding what makes experiences memorable, as well as inattention to the subjective and personal nature of experiences. This study explores the nature of individual experiences, particularly with regard to personal outcomes, emotions and meanings, by investigating tourists' experiences of the same activity in three different consumption contexts. The influence of consumption context as well as significant differences in personal outcomes were evident, and more profound and meaningful than previous research suggests. Findings point to a need to understand tourist consumption experiences beyond hedonic enjoyment of the moment, and consider their broader implications on well-being and quality of life. Implications for tourism providers and experiential marketing are discussed.